266. Multicentric evaluation of AGD (Average Glandular Dose) on 4 mammography units: Need to standardize?. (December 2018) - Marini, P.; Bona, R.; Pinna, F.; Poggiu, A.; Tamponi, M.
Abstract : Purpose: To evaluate and compare 2D images data coming from 4 identical digital mammography units, with the exception of the AEC (Automatic-Exposure-Control) calibration curve, and to verify the need to standardize the procedures. Methods and materials: In ASSL Sassari hospital, 3 Hologic Selenia Dimensions mammography units have been recently installed. During acceptance tests, evaluating at first the dose and CNR at different thicknesses and minimum detectable diameter results, we chose the same calibration curves (appointed "4" by owner) for the new units (M1-M2-M3), while we had already entered another curve (appointed "0" by owner) for the fourth machine (M4 -AOU Sassari) installed in 2011. We extracted patients' data stored in PACS through OpenRem, a free software developed by NHS (National Health Institute). We analyzed more than 2600 patients' data, making statistics on AGD, age, breast thickness and compression force. Results: You can see in the table below the ESAKs and CNRs calculated on the PMMA slabs. Even if the curve "4" brings to higher doses for major than 60 mm breast thicknesses, these are well below achievable EUREF limits, and the gain in terms of CNR and detectability is high. In the boxplot you can see the results on the AGD patients' data calculated by the machine; the data shown concern the thickness of the patients' breast over 60 mm to better highlight the differences in AGD between the three twin machines and M4. The possible influence of different thicknesses distributions between the 4 machines has been evaluated through t-test, which results are compatible with the null hypothesis. Conclusions: With the aim to improve image quality while keeping dose below EUREF limits, our next step will be to set the curve "4" on the M4 mammograph and indicate a minimum threshold for the compression force to further improve image quality.